Rationality, Behavioural Economics and Amartya Sen. Issue 2 (3rd April 2019) - Osmani, S. R.
Abstract: Recent developments in behavioural economics have posed a serious challenge to the assumption of rational choice underlying economic models. In particular, a number of so-called 'anomalies' in actual behaviour have been identified that are claimed to conflict with the implications of rational behaviour. This paper critically examines a number of such anomalies and tries to assess how far they actually challenge the precepts of rational choice. This assessment is made in the light of Amartya Sen's critique and refinement of rational choice theory. Using the lens of Sen's analysis, the paper finds that (a) many of the anomalies do not pose any challenge at all to even the narrowest version of the rational choice model, (b) some do challenge the narrow versions but not the broader ones, and (c) a few genuinely call for extending rational choice foundations of economic theory more radically – especially, in ways that Sen has been advocating for a long time.